AESTHETICS AND ECOLOGICAL SIGNIFICANCE: A PHENOMENOLOGICAL ANALYSIS OF DEW MORPHOLOGY AND WIND INTERACTION IN THE WILD - Sofyang Daeng Kelana; Gatot Ciptadi; Aulanni’am; Bagyo Yanuwiadi; Pattasang (International Journal Multidisciplinary (IJMI), 2026)
Objective: This study aims to analyze the correlation between the morphological characteristics of dewdrops—specifically their shape, spatial distribution, and optical properties—and prevailing meteorological conditions to establish a basis for natural weather prediction. Method: The methodology involves the systematic observation of dew formation on various foliar surfaces, such as grass tips and leaf blades, while monitoring variables including wind velocity, solar intensity, and cloud cover. Results: The findings indicate that high wind speeds cause dewdrops to adopt a predominantly pointed morphology, oriented toward the wind direction at the leaf apex. Conversely, the anticipation of a high-temperature day is signaled by perfectly spherical dewdrops exhibiting a brilliant light mirage effect, complemented by the presence of "sand dew" and micro-dewdrops adhering neatly to the leaf margins. Under overcast and windy conditions, however, dew accumulation is minimal, appearing blurred and localized primarily on the leaf edges with diminished optical clarity. Novelty: The novelty of this approach lies in the integration of micro-geometry and optical refraction patterns as biological proxies for atmospheric transitions, offering a unique method for local weather forecasting through the lens of botanical fluid dynamics.